Deception: The Role of Consequences - Gneezy, Uri (American Economic Review, 2005)
Abstract: This paper studies the role of consequences in a person’s decision to lie. Based on findings from an experiment with a deception game, as well as from questionnaires, I propose a simple formulation of preferences to describe deception behavior. The decision maker uses the “truth telling ” outcome as a reference level when evaluating the benefits of lying. The monetary consequences of the lie are compared to this reference level. In the formulation used in this paper the decision maker’s utility depends on her own intentions. She is selfish in the sense of maximizing her own payoffs, but sensitive to the cost her lie imposes on the other side. Sensitivity diminishes with the size of payoffs. Moreover, since perception of the counterpart’s cost is subjective. When there are differences in wealth as in employee-employer relations or a consumer-insurer interactions, the decision maker is more likely to lie the wealthier the counterpart.